Fertility Potential of Freshly Isolated Adipose Tissue-derived Stromal Cells and Bone Marrow Mesenchymal Stromal Cells in Premature Ovarian Failure - Maqbool, Tahir; Hadi, Faheem; Tahir, Sehrish; Naz, Sadia; Shahnawaz, Sajida; Awan, Sana J.; Malik, Arif (Current Women's Health Reviews, 2022)
Background: Failure to attain pregnancy or even miscarriage leads to a challenging type of infertility which is premature ovarian failure (POF). Stem cells have the ability to repair ovarian damage; adipose tissue-derived stromal cells (AT-SCs) and bone marrow mesenchymal stromal cells (BM-MSCs) have demonstrated promising regenerative abilities in several diseases, including POF. Methods: Various experiments were performed to prove the ability of AT-SCs and BM-MSCs in restoring ovarian functions; a total of 20 rats were randomly selected and assigned to four experimental groups with 5 rats in each group; 1st untreated, 2nd cyclophosphamide and busulfan, 3rd cyclophosphamide and busulfan + AT-SCs, and 4th cyclophosphamide and busulfan + BM-MSCs treated. Results: Groups 3 and 4 showed a restoration of ovarian functions in the form of an increase in weight (including body weight and ovarian weight), anti-mullerian hormone (AMH) and estradiol (E2) level, a decrease in follicle stimulating hormone (FSH) serum levels and an increase in antioxidant level of glutathione (GSH) and superoxide dismutase (SOD) in comparison with group 2. Histochemistry analysis demonstrated normal tissue distribution in the 3rd and 4th groups compared to 2nd group. Conclusion: We demonstrated the ability of AT-SCs and BM-MSCs to restore ovarian functions in females with POF.
Keywords: BM-MSCs